How will transitioning from cytology to HPV testing change the balance between the benefits and harms of cervical cancer screening? Estimates of the impact on cervical cancer, treatment rates and adverse obstetric outcomes in Australia, a high vaccination coverage country. Issue 12 (5th October 2017) - Velentzis, Louiza S.; Caruana, Michael; Simms, Kate T.; Lew, Jie‐Bin; Shi, Ju‐Fang; Saville, Marion; Smith, Megan A.; Lord, Sarah J.; Tan, Jeffrey; Bateson, Deborah; Quinn, Michael; Canfell, Karen
Abstract : Primary HPV screening enables earlier diagnosis of cervical lesions compared to cytology, however, its effect on the risk of treatment and adverse obstetric outcomes has not been extensively investigated. We estimated the cumulative lifetime risk (CLR) of cervical cancer and excisional treatment, and change in adverse obstetric outcomes in HPV unvaccinated women and cohorts offered vaccination (>70% coverage in 12–13 years) for the Australian cervical screening program. Two‐yearly cytology screening (ages 18–69 years) was compared to 5‐yearly primary HPV screening with partial genotyping for HPV16/18 (ages 25–74 years). A dynamic model of HPV transmission, vaccination, cervical screening and treatment for precancerous lesions was coupled with an individual‐based simulation of obstetric complications. For cytology screening, the CLR of cervical cancer diagnosis, death and treatment was estimated to be 0.649%, 0.198% and 13.4% without vaccination and 0.182%, 0.056% and 6.8%, in vaccinated women, respectively. For HPV screening, relative reductions of 33% and 22% in cancer risk for unvaccinated and vaccinated women are predicted, respectively, compared to cytology. Without the implementation of vaccination, a 4% increase in treatment risk for HPV versus cytology screening would have been expected, implying a possible increase in pre‐term delivery (PTD) and low birth weight (LBW) events of 19 to 35 and 14 to 37, respectively, per 100, 000 unvaccinated women. However, in vaccinated women, treatment risk will decrease by 13%, potentially leading to 4 to 41 fewer PTD events and from 2 more to 52 fewer LBW events per 100, 000 vaccinated women. In unvaccinated women in cohorts offered vaccination as 12–13 year olds, no change to lifetime treatment risk is expected with HPV screening. In unvaccinated women in cohorts offered vaccination as 12–13 year olds, no change to lifetime treatment risk is expected with HPV screening. HPV screening starting at age 25 in populations with high vaccination coverage, is therefore expected to both improve the benefits (further decrease risk of cervical cancer) and reduce the harms (reduce treatments and possible obstetric complications) associated with cervical cancer screening. Abstract : What's new? Evidence suggests that excisional treatment for lesions detected during cervical screening might increase the risk of adverse obstetric outcomes in women with cervical intraepithelial neoplasia. Whether the risk of adverse outcomes differs by screening method in the context of a woman's human papillomavirus (HPV) vaccination status was examined in this study with dynamic modeling. Compared with cytology screening every two years, primary HPV screening every five years was associated with a decreased lifetime risk of cervical cancer diagnosis and death, regardless of whether women were vaccinated against HPV. HPV screening in a vaccinated population was predicted to decrease the lifetime risk of excisional treatment.